PENGARUH GOOD CORPORATE GOVERNANCE, INSENTIF EKSEKUTIF, DEFERRED TAX EXPENSE TERHADAP TAX AVOIDANCE - Viola Silviana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2023)
This research aims to analyze the effect of Good Corporate Governance, Executive Incentives, Deferred TaxExpenses on Tax Avoidance. The population used in this research are mining sector companies that are on theIndonesian Stock Exchange in 2016-2020. By using purposive sampling, the total sample in this research was 30data from 6 companies. The research method used is panel data regression analysis using e-views 10. The resultsof this research indicate that institutional ownership, independent commissioners, executive incentives have noeffect on Tax Avoidance. Meanwhile, deferred tax expense has a negative and significant effect on tax avoidance.Simultaneously Good Corporate Governance (institutional ownership, independent commissioners), executiveincentives, and deferred tax expense have a significant effect on tax avoidance.